Social learning model on enhancing students critical thinking ability in elementary school - Utami, Ni Putu Dewina Putri; Suranata, Kadek; Yudiana, Kadek (Indonesian Institute for Counseling, Education and Therapy (IICET), 2025)
The purpose of this study was to determine the effect of the social learning model to improve students' critical thinking skills on the material of my proud region. This type of research is a quasi-experimental study with a non-equivalent Post-test only control group design. The population in this study were all students in class totaling 151. The sampling in this study used a simple random sampling technique with the results obtained, namely 10 fifth grade students as the experimental group and 19 other students as the control group. Data collection was carried out using a descriptive test method totaling 10 questions. The data were analyzed using a t-test with the results obtained so that H1 was accepted and H0 was rejected. The conclusion from the results of the data analysis in this study is that there is a significant influence of the social learning model to improve students' critical thinking skills on the material of my proud region.